Challenges with ex situ programmes - Smith, Emelie (2016)
Human activities are driving many species of wildlife towards extinction. The number of species regarded as threatened by the International Union for Conservation of Nature (IUCN) Red List of Threatened Species more than doubled between 2000-2015. This calls for future actions towards survival and recovery of endangered species. Captive breeding in zoos is a commonly used tool for maintaining biodiversity and preserving demographically stable and genetically healthy populations. However, it is clear that zoos have failed to manage sustainable populations. The level of breeding success and ultimately reintroducing animals bred in captivity into the wild varies and there are a number of important factors that have to be considered. Behaviour incompatibility, domestication effects, disease outbreaks, inadequate enclosure design and inbreeding depression are some of the factors explaining limited breeding success in zoos. A high young mortality rate and the limited breeding success seen in zoos raises concern regarding the health and welfare of zoo animals. This review illustrates the failure of getting captive populations to reproduce at rates comparable to wild populations. The results show that, this is primarily the result of species-specific socio-environmental conditions not being successfully met in captivity. Breeding success must be enhanced in breeding programs to maintain sustainable captive populations. In the future, more research is needed about which enclosure design and husbandry methods are the most beneficial as well as which social requirements need to be met in order to provide an environment that is well-adapted to the species physiological, mental and physical needs.